PTH-018 Short-term outcomes of a protocol of ESD/Hybrid-ESD as the primary resection strategy for rectal adenomas. (June 2019) - Emmanuel, Andrew; Gulati, Shraddha; Lapa, Christo; Williams, Sophie; Gunasingam, Nishmi; Burt, Margaret; Hayee, Bu; Haji, Amyn
Abstract : Introduction: ESD is rarely practiced in western centres. Given its technical difficulty, many western experts believe indications for ESD are limited. However, histopathologic diagnostic and treatment uncertainty resulting in over- or under-treatment can have grave consequences in the rectum. As a result, our unit recently opted for the exclusive use of ESD/Hybrid ESD to resect all large rectal adenomas. We report short term outcomes using this protocol for 12 months. Methods: Endoscopic resection (ER) of large (≥20 mm) colorectal adenomas were analysed and outcomes compared after adoption of an exclusive ESD resection strategy for all rectal adenomas ≥20 mm for 12 months (Period 2) compared to earlier resections (Period 1) when resection strategy was based on lesion morphology, surface characteristics and ER experience. Results: ER was performed for 185 rectal adenomas (period 1 n=154, Period 2 n=31) with a mean size of 63 mm (range 20–160 mm). ESD/Hybrid ESD was used for 97% of ER in Period 2 versus 61% in Period 1 (p<0.001). A trainee performed part or all of 52% of ERs in Period 2 versus 7% in Period 1 (p<0.001). There were no differences between time periods in complications (OR 0.4, 95% CI 0.1–3.6, p=0.44) post procedure bleeding (OR 1.0, 95% CI 0.1–8.8, p=1) or risk of stenosis (OR 1.7, 95% CI 0.2–16.7, p=0.66). Rates of submucosal invasive cancer were similar (12.9% versus 7.8%, p=0.36).There were no clinically significant perforations in either group. Conclusions: ESD/Hybrid ESD for all large rectal adenomas, even when incorporating ESD training, is feasible and safe with sufficient expertise and experience. Data for long term outcomes are desirable to evaluate potential benefits in oncological results, reduced recurrence and potential fewer additional procedures.